2014
DOI: 10.2967/jnumed.113.133876
|View full text |Cite
|
Sign up to set email alerts
|

18F-MCL-524, an 18F-Labeled Dopamine D2 and D3 Receptor Agonist Sensitive to Dopamine: A Preliminary PET Study

Abstract: PET has been used to examine changes in neurotransmitter concentrations in the living brain. Pioneering PET studies on the dopamine system have used D2 and D3 receptor (D2/D3) antagonists such as 11C-raclopride. However, more recently developed agonist radioligands have shown enhanced sensitivity to endogenous dopamine. A limitation of available agonist radioligands is that they incorporate the short-lived radioisotope 11C. In the current study, we developed the 18F-labeled D2/D3 receptor agonist (R)-(−)-2-18F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…However, 18 F-AMC20 is inferior to existing 11 C-labeled D 2/3 agonists (13,21,22) in terms of baseline striatal BP ND (0.49-0.59 vs. .0.8) and, apparently, also in terms of sensitivity to raclopride treatment. The higher nonspecific binding of 18 F-AMC20, resulting from its considerably higher lipophilicity (LogD, 2.33 6 0.03) relative to 18 F-FEt-AMC13 (LogD, 1.67 6 0.07), seems to have prevented 18 F-AMC20 from attaining a high signal-to-noise ratio despite its high affinity toward D 2/3 RHigh.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, 18 F-AMC20 is inferior to existing 11 C-labeled D 2/3 agonists (13,21,22) in terms of baseline striatal BP ND (0.49-0.59 vs. .0.8) and, apparently, also in terms of sensitivity to raclopride treatment. The higher nonspecific binding of 18 F-AMC20, resulting from its considerably higher lipophilicity (LogD, 2.33 6 0.03) relative to 18 F-FEt-AMC13 (LogD, 1.67 6 0.07), seems to have prevented 18 F-AMC20 from attaining a high signal-to-noise ratio despite its high affinity toward D 2/3 RHigh.…”
Section: Discussionmentioning
confidence: 91%
“…The scope of use of 11 C tracers is limited by the short half-life of 11 C (20.4 min), whereas tracers labeled with longer-living radioisotopes such as 18 F (half-life, 109.8 min) have a much greater potential. (R)-(2)-2-18 F-fluoroethoxy-N-n-propylnorapomorphine ( 18 F-MCL-524), an 18 F-labeled apomorphine derivative, showed promising results in monkeys (13) but has not yet been reported to be used in humans.…”
mentioning
confidence: 99%
“…Apomorphine analogs, 11 C-NPA in PET studies of nonhuman primates clearly showed binding to the caudate-putamen, similar to that found for 11 C-raclopride (Finnema et al, 2009; Hwang et al, 2005). More recently, agonists 18 F-MCL-524, apomorphine analogs (Finnema et al, 2014; Sromek et al, 2014) and 18 F-aminomethylchroman analogs (Shalgunov et al, 2015a,b) have been reported for imaging dopamine D2 and D3 receptors. 11 C-PHNO is a modified aminotetralin derivative and has high-affinity for D2 and D3 receptor subtypes thus suggesting that PHNO binds to D2-high affinity state (HA) and D3 receptors.…”
Section: | Introductionmentioning
confidence: 99%
“…Antagonists bind with equal affinity to the two affinity states of the receptor and do not provide information on the fraction of receptors in the high-affinity state. To overcome this limitation, agonist radioligands, binding readily with the high-affinity state D 2 receptor, have recently been developed, including 18 F-MCL-524 (Finnema et al, 2014), 11 C-NPA (Hwang et al, 2000), 11 C-MNPA (Finnema et al, 2005), and 11 C-4-propyl-9-hydroxynaphthoxazine (Wilson et al, 2005). The advantage of these agonist radioligands is that they are more displaceable than the antagonist radiotracer [ 11 C]raclopride after an acute psychostimulant-challange.…”
Section: Resultsmentioning
confidence: 99%